Analysis of Halal Standards and Poultry Slaughterhouse Strategies as A Guarantee of Product Protection for Consumers at Pak Kus Poultry Slaughterhouse - , M. Abasri; Isnaeni, Nurida; Enggrani Fitri, Lucky (Bertuah Jurnal Syariah dan Ekonomi Islam, 2025)
This study aims to determine how the implementation of halal standards for Pak Kus poultry slaughterhouses, what are the obstacles in implementing halal standards for Pak Kus poultry slaughterhouses, and what strategies are used in implementing halal standards for Pak Kus poultry slaughterhouses. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that Pak Kus poultry slaughterhouses still face various challenges in implementing halal standards, such as lack of understanding of certification procedures, limited facilities, and lack of supervision from related institutions. However, poultry slaughterhouse owners carry out strategies such as providing training to workers, improving infrastructure and collaborating with halal certification institutions. With better implementation of halal standards, it is hoped that Pak Kus poultry slaughterhouses can obtain halal certification and continue to increase consumer trust and loyalty.